Muscle Synergies and Coherence Networks Reflect Different Modes of Coordination During Walking - Kerkman, Jennifer N.; Bekius, Annike; Boonstra, Tjeerd W.; Daffertshofer, Andreas; Dominici, Nadia (Frontiers in Physiology, 2020)
When walking speed is increased, the frequency ratio between the arm and leg swing switches spontaneously from 2:1 to 1:1. We examined whether these switches are ac-companied by changes in functional connectivity between multiple muscles. Subjects walked on a treadmill with their arms swinging along their body while kinematics and surface electromyography (EMG) of 26 bilateral muscles across the body were record-ed. Walking speed was varied from very slow to normal. We decomposed EMG enve-lopes and intermuscular coherence spectra using non-negative matrix factorization (NMF), and the resulting modes were combined into multiplex networks and analysed for their community structure. We found five relevant muscle synergies that signifi-cantly differed in activation patterns between 1:1 and 2:1 arm-leg coordination and the transition period between them. The corresponding multiplex network contained a single module indicating pronounced muscle co-activation patterns across the whole body during a gait cycle. NMF of the coherence spectra distinguished three EMG fre-quency bands: 4-8 Hz, 8-22 Hz, and 22-60 Hz. The community structure of the multi-plex network revealed four modules, which clustered functional and anatomical linked muscles across modes of coordination. Intermuscular coherence at 4-22 Hz between upper and lower body and within the legs was particularly pronounced for 1:1 arm-leg coordination and was diminished when switching between modes of coordination. These findings suggest that the stability of arm-leg coordination is associated with modulations in long-distant neuromuscular connectivity.